El aprendizaje basado en problemas en la formación de profesionales de la salud - Restrepo Gómez, Bernardo; García Ospina, Norbey; Ceballos Velásquez, María Elena; Arango Rave, Angela María; Aponte Salazar, Amalia; Bernal Alvarez, Tomas; Ramírez Jaramillo, Luz Angela; Gómez Echeverri, Mariela; Alzate Yepes, Teresita; Calvo Moore, Yadira; Beltrán Urán, Haydee; Sierra Lopera, Jorge Luis; et al. (Investigación y Educación en Enfermería, 2013)
.